Child Marriage Indications a violation of International and National Laws - Jan, Attaullah (Journal of Peace, Development and Communication, 2022)
More than 60 million women throughout the world are affected by adolescent marriage, which is defined as marriage before the age of 18. In low-income countries including, Pakistan, this is increasingly widespread. Despite the fact that the universal age for women to marry is 18, but girls are married earlier in poor countries, particularly in South Asian countries. Even in the twenty-first century, child marriage is common around the world. Early marriage is prohibited by national and international laws. Despite of it, child marriages are in practices because no punishment is given to those people who are involved in it. If the proper implement of laws, child marriage can be ended from the world. However, it failed to end child marriage because no legal action is given against involved people. The literature review endeavor to shed light on the law situation of child marriage, focusing legal aspects of violation of child marriage. The breach of international and state law by underage marriage is discussed in this study.